1999
DOI: 10.1542/peds.103.3.e32
|View full text |Cite
|
Sign up to set email alerts
|

Chest Physiotherapy in Cystic Fibrosis: Improved Tolerance With Nasal Pressure Support Ventilation

Abstract: ABSTRACT. Objective. Chest physiotherapy (CPT) is an integral part of the treatment of patients with cystic fibrosis (CF). CPT imposes additional respiratory work that may carry a risk of respiratory muscle fatigue. Inspiratory pressure support ventilation (PSV) is a new mode of ventilatory assistance designed to maintain a constant preset positive airway pressure during spontaneous inspiration with the goal of decreasing the patient's inspiratory work. The aim of our study was 1) to evaluate respiratory muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
78
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(81 citation statements)
references
References 28 publications
2
78
0
1
Order By: Relevance
“…3,4,28,29 Dunnink et al 4 suggest that the increased work of breathing due to airway obstruction could cause an effect of conditioning the respiratory muscles. On the contrary, some studies 5,12,30,31 showed a reduction of respiratory muscle strength, associating this finding with hyperinflation and malnutrition. Furthermore, Dassios et al 32 showed that maximum respiratory pressures were significantly diminished in subjects with no severe lung disease; however, no correlation between P Imax and BMI was found.…”
Section: Discussionmentioning
confidence: 96%
“…3,4,28,29 Dunnink et al 4 suggest that the increased work of breathing due to airway obstruction could cause an effect of conditioning the respiratory muscles. On the contrary, some studies 5,12,30,31 showed a reduction of respiratory muscle strength, associating this finding with hyperinflation and malnutrition. Furthermore, Dassios et al 32 showed that maximum respiratory pressures were significantly diminished in subjects with no severe lung disease; however, no correlation between P Imax and BMI was found.…”
Section: Discussionmentioning
confidence: 96%
“…In regions with mild to severe obstruction, increased velocity and turbulent flows seem to promote deposition through the impaction mechanism, resulting in a concentration of radio-aerosol in "hot spots" near the obstructed areas. 33 The radio-aerosol penetration index was higher in the central regions of the lungs in both groups, thereby reducing the percentage that reached the intermediate and peripheral regions. Fauroux et al 33 found a higher radioaerosol penetration index in the NIV ϩ nebulizer group, but the comparison of those data to our results is limited, as the patients assessed in the Fauroux et al study had cystic fibrosis, and the obstruction measured by the spirometry differed from those patients with asthma.…”
Section: Discussionmentioning
confidence: 82%
“…Previous studies described similar results, with flow values of around 40 L/min contributing to less peripheral deposition. 18,33 The analysis of deposition in the vertical differences revealed greater deposition in the middle third in comparison to the upper and lower thirds, and in the lower third, in comparison to the upper third, in both lungs. However, no difference in radio-aerosol counts was detected between the upper and lower thirds of the left lung in the control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some papers report that hyperinflation combined with malnutrition may be a factor predisposing to ventilatory muscle weakening 4,6,7 . On the other hand, chronic cough and increase in ventilatory effort seem to favor muscle strength 5,8 .…”
Section: Introductionmentioning
confidence: 99%